Symmetric wideband five port reflectometer for microwave-imaging based brain injury diagnosis - Hossain, Toufiq Md. author (School of Computer and Communication Engineering, 2018)
MWI system requires the combination of lower and higher frequencies for higher penetration depth and better image resolution respectively, as mentioned earlier. 1 to 4 GHz frequency can be considered the optimum range for brain injury diagnosis perspective. Operating frequency of the FPR is targeted to be within 1 to 4 GHz. The challenges in broadening the bandwidth revolve around the fulfillment of the criteria of matching the ports as well as maintaining the transmission coefficient at a value of 0.5 in terms of magnitude. Moreover, the phase difference between the transmission coefficients should be 120.